2018
DOI: 10.3390/nu10122012
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte n-6 Fatty Acids and Risk for Cardiovascular Outcomes and Total Mortality in the Framingham Heart Study

Abstract: Background: The prognostic value of erythrocyte levels of n-6 fatty acids (FAs) for total mortality and cardiovascular disease (CVD) outcomes remains an open question. Methods: We examined cardiovascular (CV) outcomes and death in 2500 individuals in the Framingham Heart Study Offspring cohort without prevalent CVD (mean age 66 years, 57% women) as a function of baseline levels of different length n-6 FAs (18 carbon, 20 carbon, and 22 carbon) in the erythrocyte membranes. Clinical outcomes were monitored for u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 29 publications
0
10
0
1
Order By: Relevance
“…A systematic review reported that N-3 and N-6 PUFAs have competing roles in the production of anti-inflammatory and inflammatory eicosanoids 21 . Some studies have suggested that the EPA:AA ratio was associated with CHD risk, but they could not find a consistent conclusion regarding the same 34 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A systematic review reported that N-3 and N-6 PUFAs have competing roles in the production of anti-inflammatory and inflammatory eicosanoids 21 . Some studies have suggested that the EPA:AA ratio was associated with CHD risk, but they could not find a consistent conclusion regarding the same 34 .…”
Section: Discussionmentioning
confidence: 94%
“…The clinical value of N-6 PUFAs for total mortality and CVD risks remains controversial 21,34 . In the Framingham Heart Study, higher marine N-3 PUFA concentrations were related to reduced CVD, ischaemic stroke, and mortality risks.…”
Section: Discussionmentioning
confidence: 99%
“…The cardiovascular effects of omega-6 FA are still controversial, with some studies and meta-analysis indicating a protective effect of linoleic acid (LA), and possibly of arachidonic acid (AA), on incident CV disease [4] and other studies reporting no or a possible harmful association of omega-6 FA with CV events [16,17]. Our previous study was in line with the hypothesis of a possible beneficial effect of arachidonic acid on CV risk factors and non-alcoholic fatty liver disease [3].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, ratios like n-6:n-3 18 or AA:EPA 19 have been promoted as better summary metrics of PUFA status than either family alone. This perspective has, however, been criticized on both theoretical [20][21][22][23] and evidential [24][25][26] bases.…”
Section: Discussionmentioning
confidence: 99%
“…The Framingham Heart Study is a longitudinal community-based cohort study that was initiated in 1948. The selection criteria for the Framingham Offspring Cohort and the Framingham Omni Cohort have previously been described 4,5 (http://nhlbi.nih.gov/about/framingham). Briefly, adult children of the Original cohort were recruited in 1971 into the Framingham Offspring Cohort.…”
Section: Methodsmentioning
confidence: 99%